Ecopost: Eco-critical discourse analysis of wwf-Philippines’ captions - Jhoan Cristine R. Fernando; Rodolfo P. Dizon Jr (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
This study explores the eco-critical discourse analysis of eco-friendly language used in the 2024 captions posted by WWF-Philippines on Facebook. It aims to examine how ecolinguistic features such as metaphors, narratives, persuasive language, and intertextuality are employed to promote environmental awareness and sustainability. Through a qualitative descriptive approach and using criterion sampling, 38 selected captions were analysed to categorize ecological discourse as eco-beneficial, eco-ambivalent, or eco-destructive. The study also investigates how these discourses reflect the WWF-Philippines’ ecosophy, emphasizing interconnectedness, care for living beings, and environmental justice. Results reveal that metaphors and persuasive language are the most prominent features used to inspire environmental consciousness. Most captions conveyed eco-beneficial discourse, encouraging collective responsibility, emotional engagement, and positive environmental actions. Findings highlight the importance of strategic language use in fostering environmental advocacy on digital platforms. The study contributes to the growing field of ecolinguistics by providing insights into the role of language in shaping ecological awareness and promoting sustainable behaviours through social media communication. This study shows how language can be a powerful tool for promoting social media action and raising environmental awareness.